System of antioxidant protection of young cattle under cadmium load : cт. - Smychok, L. Z.; Gutyj, B. V. et. al.; Vus, U. M.; Martyshuk, T. V.; Sobolta, A. G.; Vysotskij, A. O.; Magrelo, V. R. (Stepan Gzhytskyi National University of Veterinary Medicine and Biotechnologies, 2023)
It is known that free radical oxidation of lipids is an essential stage in the influence of heavy met-als on the animal body. That is why the work aimed to investigate the indicators of the antioxidant system in young cattle under conditions of cadmium loading. For research, 15 clinically healthy six-month-old bulls of the black and spotted breed were selected, from which 3 groups of five animals were formed. The animals in the control group were on a regular diet. The animals of the experimental groups with compound feed were fed cadmium chloride in doses of 0.03 and 0.05 mg/kg of body weight. Feeding young cattle with cadmium chloride feed caused a decrease in the activity of the en-zyme system of antioxidant protection of their body. These changes are confirmed by a decrease in their blood activity of superoxide dismutase by 31 %, catalase by 13.4 %, glutathione peroxidase by 23.2 %, glutathione reductase by 22.2 %, and glucose-6-phosphate dehydrogenase by 32.4 %, respec-tively. A decrease in the level of indicators of the non-enzymatic link of the system of antioxidant pro-tection of the body of young cattle under cadmium load was also established, where, accordingly, a decrease in the content of reduced glutathione was established – by 10.4 %, selenium – by 14.8 %, vitamin A – by 31.3%, of vitamin E – by 30.8% in their blood compared to the control. It is worth noting that on the sixteenth and twenty-fourth days of the experiment, the lowest value of the enzymatic and non-enzymatic links of the antioxidant protection systems of young cattle under conditions of cadmium loading was observed. In the future, a practical scheme for preventing cadmium toxicosis in young cattle by studying indicators of the antioxidant system is planned.
Keywords: bulls; antioxidant system; cadmium; бики; кадмій